PENGARUH MEDIA VIDEO TUTORIAL YOUTUBE TERHADAP AKTIVITAS BELAJAR PJOK PADA KELAS X DI SMAN 2 SUKATANI - Reza Maulana; Fauzi Miftakh, Aria Kusuma Yuda Ryanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of using YouTube video tutorial media on students' learning activities in the subject of Physical Education, Sports, and Health (PJOK) for tenth- grade students at SMAN 2 Sukatani. The background of this research is based on the low level of student engagement in PJOK classes, which are still largely dominated by conventional teaching methods, resulting in decreased interest, focus, and learning motivation among students. In the digital era, the use of innovative learning media such as video tutorials has become an alternative to enhance the effectiveness of the learning process. This research uses a quantitative approach with a quasi-experimental method and a One Group Pretest-Posttest Design. The sample consisted of 70 students from classes X-1 and X- 2. The research instrument used was a learning activity questionnaire, which included internal factors (psychological, physical, personal), external factors (family, school, and social environment), and aspects of learning activity using digital media. Data analysis showed that the use of YouTube video tutorials significantly increased students’ learning activity. This media helped students to become more focused, motivated, and actively engaged in PJOK learning. The findings of this study indicate that video tutorial-based digital media can be an effective alternative in improving student participation and motivation. Therefore, PJOK teachers are encouraged to be more creative in integrating technology, particularly video tutorials, into the learning process. This study also provides practical contributions to the development of more engaging, interactive, and relevant teaching strategies in line with technological advancements.